The Role of Substance P in Chronic Low Back Pain (CLBP) - Rachmawati, Yusnita (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Low Back Pain is one of the disease that causing global disability in the worldwide. In the past 10 years, prevalence of LBP has not decreased, it makes global burden increase substantially. Chronic low back pain(CLBP) is pain that is almost experienced daily by patients in the lower back region in a period of more than 3 months. Chronic low back pain is a mixture of pain that arises through nociceptive and neuropathic mechanisms. Over the past decade, numerousÂ guidelines have been usedÂ in the management of CLBP. Problems that are still a controversy include the management of pain. The mechanism of many treatment measures is still in the low to moderate effectiveness stage, so that the pain management target is not optimal. Substance P is a neuropeptide that releaseÂ both in acute and chronic pain. Therefore study about mechanisms that affect SP release may show important information regarding pathological alterations in pain perception.